Anthropogenic and meteorological drivers of 1980–2016 trend in aerosol optical and radiative properties over the Yangtze River Basin. (15th February 2020) - He, Lijie; Wang, Lunche; Huang, Bo; Wei, Jing; Zhou, Zhigao; Zhong, Yang
Abstract: Since the reform and opening up, Yangtze River Basin (YRB) with rapid industrialization and urbanization has become the most important source of anthropogenic aerosol emissions. However, the drivers of long-term trends in aerosol optical and radiative properties have not yet been adequately clarified. In this study, the multiple linear regression (MLR) and geographically weighted regression (GWR) models were employed to quantitatively estimate the impact of anthropogenic emissions, land use cover changes, urban forms and meteorological conditions on aerosol optical depth (AOD) and direct radiative effect (ADRE). A trend analysis revealed that over-increasing trends in AOD and ADRE were curbed around 2010. In addition, there were remarkable regional differences with respect to the effects of anthropogenic and meteorological factors on aerosol trends. Anthropogenic emissions dominated the growth of AOD and ADRE in the middle and lower reaches of the YRB after 1980, but not in the source of the YRB. Besides, the expansion of built-up land (at a 5.79% rate of increase) during 1980–2010 mainly occurred in the YRD, CC, and SB, which thus accelerated the growth of AOD and ADRE. Furthermore, AOD-ADRE was positively related to the patch area (CA), patch number (NP), and patch edge density (ED), but negatively associated with the largest patch index (LPI). It indicated that a compact urban form could mitigate aerosol loadings by enhancing urban connectivity and reducing vehicle dependence. Finally, a rise in temperature was found to be one of the driving factors for AOD growth. However, the theoretical growth in AOD (0.00084 yr −1 ) in relation to temperature rise was far less than the actual growth (0.0065 yr −1 ). Graphical abstract: Regression coefficients of AOD and meteorlogical condition based on MLR model. Image 1 Highlights: The over-increasing trends in AOD and ADRE were curbed around 2010. Changes in emissions dominated the growth of AOD and ADRE after 1980. The expansion of built-up land accelerated the growth of AOD and ADRE. A compact urban form was conductive to reducing AOD and ADRE. The temperature rise has led to a growth of AOD by 0.00084 per year since 1980.